Nursing Care In The Prevention And Management Of Catheter-Associated Urinary Tract Infections (Cautis): An Evidence-Based Review (The Review of Diabetic Studies, 2025)
Catheter-associated urinary tract infections (CAUTIs) represent one of the most common and preventable healthcare-associated infections (HAIs) globally, posing a significant threat to patient safety and creating a substantial economic burden on healthcare systems. Nurses, positioned at the center of patient care, play the most critical role across the entire continuum of urinary catheterization. This review synthesizes current, evidence-based literature on nursing-led interventions designed to prevent and manage CAUTIs. The analysis is structured around four foundational pillars of nursing practice: ensuring the appropriate use of indwelling catheters by avoiding unnecessary placement and championing alternatives; adhering to strict aseptic technique during insertion; providing diligent, evidence-based daily maintenance of the catheter and drainage system; and facilitating the timely removal of catheters through vigilant daily assessment and nurse-driven protocols. Furthermore, this review examines the nurse's role in surveillance, including the early recognition of CAUTI signs and symptoms, proper specimen collection, and effective communication within the interprofessional team. System-level supports, such as prevention bundles, ongoing education, performance feedback, and patient engagement, are discussed as essential components for creating a sustainable culture of safety. By empowering nurses with knowledge, autonomy, and evidence-based protocols, healthcare organizations can significantly reduce CAUTI rates, decrease patient morbidity and mortality, and improve the overall quality and safety of care.